The advancement of precast development in India:A Critical survey of challenges & benefits withinthe rising residential sector - Abhi K. Rakholiya,Pravin R.Minde, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In India, traditional construction processes must be improved by the use of contemporary technologies. For the past fifty years, precast concrete construction technology has consistently provided efficient and improved quality. Modern tools and technologies can improve quality while using fewer resources such as time, money, personnel, and materials. The concept of “built it fast” within the most conservative way has not changed since the beginning; in any case, unused advances have been created to suit present-day world development.We are currently on the cusp of large-scale urbanization, which means we are facing a massive need for housing construction. With a financial development rate of 7.5 percent over the last five years, India is the world's fastest developing nation. Pre-cast concrete development innovation is one such arrangement. Pre-cast innovation, the so-called unusual strategy within the Indian field, can encourage both speed and quality and abuse the preferences that ventures offer in terms of reiterations and volume by creating structural components in a productive work environment with access to specialized abilities and hardware to reduce fetched and time uses on the location while improving the quality and consistency of Pre-cast innovation, the so-called unusual strategy within the Indian field can encourage both speed and quality and abuse the preferences that ventures offer in terms of reiterations.In the industry, precast concrete technologies are now widely used and used. Many countries currently have and deploy thermal, acoustic, and seismic resistant technology, as well as visually beautiful architectural pre-cast facades for structures.